Inverse problems for a generalized subdiffusion equation with final overdetermination - Kinash, Nataliia; Janno, Jaan (Mathematical Modelling and Analysis, 2019)
We consider two inverse problems for a generalized subdiffusion equation that use the final overdetermination condition. Firstly, we study a problem of reconstruction of a specific space-dependent component in a source term. We prove existence, uniqueness and stability of the solution to this problem. Based on these results, we consider an inverse problem of identification of a space-dependent coefficient of a linear reaction term. We prove the uniqueness and local existence and stability of the solution to this problem.